2013
DOI: 10.1007/s00125-013-3109-4
|View full text |Cite|
|
Sign up to set email alerts
|

Mesenchymal stromal cells improve transplanted islet survival and islet function in a syngeneic mouse model

Abstract: Co-transplantation of MSCs may lead to improved islet function and survival in the early post-transplantation period in humans receiving islet transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 42 publications
6
77
0
1
Order By: Relevance
“…These range of activities led Arnold Caplan to suggest changing the "MSC" acronym to "medicinal signaling cells" [163] . Cotransplantation of islets and MSCs seeded on naked scaffold enhanced islet function [164,165] , and similar advantage were de monstrated following coencapsulation of islets and MSCs [166,167] . In our hands, rat islets coencapsulated with marginal mass of pancreatic MSCs and cultured for 2 wk demonstrated enhanced insulin secretion capacity and better survival rate (Barkai et al, unpublished data).…”
Section: Controlling Inflammationmentioning
confidence: 83%
“…These range of activities led Arnold Caplan to suggest changing the "MSC" acronym to "medicinal signaling cells" [163] . Cotransplantation of islets and MSCs seeded on naked scaffold enhanced islet function [164,165] , and similar advantage were de monstrated following coencapsulation of islets and MSCs [166,167] . In our hands, rat islets coencapsulated with marginal mass of pancreatic MSCs and cultured for 2 wk demonstrated enhanced insulin secretion capacity and better survival rate (Barkai et al, unpublished data).…”
Section: Controlling Inflammationmentioning
confidence: 83%
“…MSCs also secrete a wide range of factors that induce tissue repair and angiogenesis (23); release microvesicles containing microRNAs, lipids, and proteins (24); and act as a stromal cell support system by laying down extracellular matrix (ECM), which may provide a physical niche for transplanted cells (25). Recent studies, including our own (6)(7)(8), have established that MSCs have the capacity to enhance islet function in vitro (4,(9)(10)(11) and have demonstrated that cotransplantation of islets and MSCs into diabetic animals improves islet functional survival and glycemic control (3,5,8,18,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Prediabetes was defined as significantly increased 2-h blood glucose values at unchanged nonfasting blood glucose levels. Islet isolation and transplantation to the anterior chamber of the eye were performed as previously described (25)(26)(27)(28). Transplanted islets were allowed to engraft fully for at least 4 weeks before the start of any in vivo experiments.…”
Section: Diet-induced Obesity Modelmentioning
confidence: 99%